2010
DOI: 10.3816/cbc.2010.n.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Structured Weight-Bearing Exercise Program on Bone Metabolism Among Breast Cancer Survivors: A Feasibility Trial

Abstract: Purpose Treatments for breast cancer, specifically hormonal therapy, accelerate bone loss (BL) among breast cancer survivors, leading to osteoporosis and an increase in fracture risk. Tai Chi Chuan (TCC) is a moderate form of weight-bearing exercise, equivalent to walking, and it has been shown to improve aerobic capacity and strength among breast cancer survivors and might also be effective in slowing bone loss in breast cancer survivors. This pilot study compared the influence of TCC with that of standard su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 45 publications
(48 reference statements)
1
75
0
1
Order By: Relevance
“…Primary endpoints were serum and urine bone turnover markers as well as cytokines including IL-2, IL-6, and IL-8. Compared to the standard support therapy, the Tai Chi group had significantly increased levels of bone formation markers and IL-6 levels (P = 0.00), as well as decreased bone resorption markers (P = 0.05) and a trend for decreased 136 Integrative Oncology IL-2 (P = 0.08) levels [79]. These anti-inflammatory and bone metabolism changes should be further tested in larger-sized studies.…”
Section: Music Therapymentioning
confidence: 92%
See 1 more Smart Citation
“…Primary endpoints were serum and urine bone turnover markers as well as cytokines including IL-2, IL-6, and IL-8. Compared to the standard support therapy, the Tai Chi group had significantly increased levels of bone formation markers and IL-6 levels (P = 0.00), as well as decreased bone resorption markers (P = 0.05) and a trend for decreased 136 Integrative Oncology IL-2 (P = 0.08) levels [79]. These anti-inflammatory and bone metabolism changes should be further tested in larger-sized studies.…”
Section: Music Therapymentioning
confidence: 92%
“…• A small feasibility study compared Tai Chi Chuan with standard support therapy in 16 breast cancer patients to evaluate bone metabolism and cytokine markers. Patients were randomized into either 12 weeks of 60-min Tai Chi Chuan sessions given 3 times per week or to the same schedule of standard support therapy consisting of classroom sessions emphasizing coping strategies, cohort support, and group unity [79]. The support therapy group was instructed to not alter their current level of physical activity during the 12-week study.…”
Section: Music Therapymentioning
confidence: 99%
“…Previous researches in BCS showed that TC improves functional capacity (Mustian et al, 2006), QoL (Mustian et al, 2008), and self-esteem (Mustian et al, 2004) and can regulate growth factors and binding proteins associated with weight gain and bone loss (Peppone et al, 2010;Janelsins et al, 2011). However, to our knowledge, these studies have a relatively small sample size with wide variation and convey mixed and inconclusive results.…”
Section: Introductionmentioning
confidence: 91%
“…Pretrial physical activity eligibility criteria varied widely across studies, with none requiring participants to be completely inactive. Trials targeted postmenopausal women (Irwin et al, 2009;Waltman et al, 2010;Winters-Stone, Dobek, et al, 2012), premenopausal or recently menopausal women (Swenson et al, 2009;Winters-Stone, Dobek, et al, 2012), or included participants of mixed menopausal status (Peppone et al, 2010;Saarto et al, 2012;Swartz et al, 2007) with two of the latter considering premenopausal and postmenopausal women together and separately (Saarto et al, 2012;Schwartz et al, 2007). Trials enrolled small ( N ϭ 16) to large ( N ϭ 573) samples, with three of the eight trials enrolling Ͼ 100 participants (Saarto et al, 2012;Waltman et al, 2010;Winters-Stone, Dobek, et al, 2011).…”
Section: Exercise For Bone Healthmentioning
confidence: 97%
“…Eight controlled trials have been conducted (Irwin et al, 2009;Peppone et al, 2010;Saarto et al, 2012;Schwartz, WintersStone, & Galluci, 2007;Swenson et al, 2009;Waltman, Ott, Twiss, Gross, & Lindsey, 2009;Winters-Stone, Dobek, et al, 2012;Winters-Stone, Dobek, et al, 2011), with one trial reporting different bone outcomes in separate publications (Nikander et al, 2012;Saarto et al, 2012) and one trial reporting an additional moderator analysis in another publication (Winters-Stone, Leo, & Schwartz, 2012). Four of the controlled trials compared an exercise group to a usual care comparison group (Irwin et al, 2009;Peppone et al, 2010;Saarto et al, 2012;Schwartz et al, 2007), two compared the experimental exercise group to a placebo-stretching group (Winters-Stone, Dobek, et al, 2011;Winters-Stone, Dobek, et al, 2012), and two had pharmacologic comparison groups with one comparing exercise versus drug therapy (Swenson et al, 2009) with one comparing drug therapy alone to drug therapy plus exercise (Waltman et al, 2010).…”
Section: Exercise For Bone Healthmentioning
confidence: 99%